A Simplified Analytic Treatment of Shell-Effects in Metal Clusters - Kotsos, B. A.; Grypeos, M. E. (HNPS Advances in Nuclear Physics, 2020)
A simplified treatment of shell-effects in metal clusters, such as those of Na, is considered. This treatment is carried out by means of an approximate scheme based on the spherical harmonic oscillator jellium model and its advantage is that it suggests the possibility quantities of physical interest to be calculated analytically. As a result, the variation of these quantities with the number of the valence electrons of the atoms in the cluster could be given explicitly in certain cases.